Evaluating the administrative performance of sports clubs from the viewpoint of the General Authority for Youth and Sports, Libya - Al-Nafiru, Hassan Muhammad Muhammad; Chortane, Sabri Gaied; Amar, Imen Ben; Amara, Sofiene; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2023)
The study aimed to identify the evaluation of the administrative performance of sports clubs from the point of view of the General Authority for Youth and Sports Libya, and to identify the level of knowledge of the study sample evaluation criteria in the areas of administrative performance of sports clubs in Libya, and the study population included two functional categories, namely senior management, middle management and sports offices in the regions of the employees of the General Authority for Youth and Sports previously Ministry of Sports currently, the study sample consisted of (79 ) people. The studied sample of the role of evaluating the administrative performance of sports clubs from the point of view of the General Authority for Youth and Sports came with a moderate degree with an arithmetic average of (3.28). The study recommended the work of time programs to monitor the performance of work within the corridors of the club in all financial, administrative and technical fields, lectures and workshops in all parts of Libya in order to introduce the evaluation and its importance.